Novel Synthetic and Mechanistic Approach of TFA Catalysed Friedländer Synthesis of 2‐Acylquinolines from Symmetrical and Unsymmetrical 1, 2‐Diketones with o‐Aminoarylketones. Issue 21 (21st December 2016) - Satheeshkumar, Rajendran; Shankar, Ramasamy; Kaminsky, Werner; JayarampillaiRajendra Prasad, Karnam
Abstract: In focussing on the reaction mechanism of Friedländer synthesis in the presence of acid catalysts, novel regioselective synthesis of 2‐acetylquinolines from reacting a symmetrical 1, 2‐diketone, butan‐2, 3‐dione with o ‐aminoarylketones was reported. Similar condensation of o ‐aminoarylketones with unsymmetrical 1, 2‐diketone, pentan‐2, 3‐dione leads to the formation of 2‐propanoylquinoline. The proposed reaction mechanism is scrutinized through density functional calculations at B3LYP/6‐311G (d, p) and M06‐2X/6‐311G (d, p) level of theory and also all the relative energy barriers and activation energies of the reaction steps are found to be minimum at above level of theory. Results from theoretical study have further strengthened by FT‐IR, FT‐NMR chemical shifts and structural parameters which were achieved with the same level of theory and the corresponding results were substantiate with experimental observations. Abstract : An attempt to device a novel synthetic route for 2‐acetylquinolines from symmetrical 1, 2‐diketone, butan‐2, 3‐dione with o ‐aminoarylketones in acid catalysed conditions yielded via Friedländer synthetic method. The same condensation of o ‐aminoarylketones with unsymmetrical 1, 2‐diketone, pentan‐2, 3‐dione under similar condition has led to the formation of 2‐propanoylquinoline in major yield. When the above reaction was carried out using acetic acid instead of TFA acid afforded two products, 2‐propanoylquinolines as a major product and 2‐acetyl‐3‐methylquinolines as a minor product.